ChemInform Abstract: Total Syntheses of Eudistomins Y1—Y7 by an Efficient One‐Pot Process of Tandem Benzylic Oxidation and Aromatization of 1‐Benzyl‐3, 4‐dihydro‐β‐carbolines. Issue 45 (14th October 2013) - Trieu, Tien Ha; Dong, Jing; Zhang, Qiang; Zheng, Bo; Meng, Tian‐Zhuo; Lu, Xia; Shi, Xiao‐Xin
Abstract The first total synthesis of eudistomin Y7 (Ia) and total syntheses of eudistomins Y1‐Y6 (Ib‐g) are described.